Pencegahan Penyakit Parasit Gigi Melalui Penyuluhan Dan Pendampingan Menggosok Gigi Anak Sd Sungai Tabuk Keramat I Martapura - Rahmawati, Ida; Rifqoh; Fansurna, Anderi (UPPM Poltekkes Kemenkes Banjarmasin, 2022)
Based on data obtained from the Sungai Tabuk 1 Health Center in 2019, there were 2848 patients with dental problems at the puskesmas, while 175 pediatric patients. (Puskesmas Sungai Tabuk 1, 2019). Based on data from dental and oral health screening by the Sungai Tabuk 1 Health Center, SDN Sungai Tabuk Keramat 1 stated that 90% of students who had their teeth checked had dental caries problems. For deciduous teeth, a def-t of 347 was obtained with an average number of def-t = 2.60 While for permanent teeth, a DMF-T examination result of 218 was obtained with an average lift of DMF-T = 1.63. From the results of the examination carried out, as many as 12 teeth were filled with ART. Microscopic laboratory examination results on 131 children of SDN Sei Tabuk Keramat 1 out of 16 (12.2%) children with non-cavities as many as 10 children (7.6%) with negative results, but there were 6 children (12.2%) with positive dental parasite test results Entamoeba gingivalis. Increased knowledge of students on how to brush their teeth properly and correctly. The def-t and DMF-T numbers belong to the low category with a def-t value of 346: 131 obtained an average of 2.64 and a DMF-T value of 216: 131 obtained an average of 1.64. Dental parasites were detected in laboratory in children of SD Sei Tabuk Keramat I positive for Entamoeba histolytica as many as 40 children (30.5%) while negative results as many as 91 children (69.5%). It is expected that students at SDN Sei Tabuk Keramat I maintain and improve their dental and oral hygiene. It is expected that the participation of parents will maintain healthy teeth and mouth. Keywords: Dental caries, parasites